Effect of trace elements (Fe3 +, Mg2+, S6+) on the hydration mechanisms of alkali-activated coal gangue - Jie Li; Shunchang Yin; Hao Li; Changwang Yan; Ju Zhang; Yue Wu; Shuguang Liu (Case Studies in Construction Materials)
To better understand the influence of trace elements in coal gangue (CG) on the hardening mechanism of alkali-activated coal gangue cementitious materials (AACG), this study selected Fe, Mg, and S as the primary trace elements based on variations in the chemical composition of CG from different origins. AACG was prepared by adding Fe2O3, MgO, and SO3 into coal gangue at proportions of 0 %, 0.5 %, 1.0 %, 1.5 %, and 2.0 %. The compressive strength test, nuclear magnetic resonance (NMR) porosity analysis, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TG-DTG), and scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) were employed to systematically investigate the compressive strength, hydration products, and microscopic morphology of AACG cementitious materials. The results indicated that Fe₂O₃ partially facilitated the formation of zeolite-like aluminosilicates in AACG cementitious materials and significantly improved the pore structure, reducing porosity by 38.2 % compared to the control group at a 2 % dosage. Increasing the MgO concentration enhanced the activity of CG, raising the pyrolysis temperature of N-A-S-H and aluminosilicate gels from 110.19 °C to 117.86 °C in TG-DTG analysis at 2 % MgO doping. Additionally, SEM images revealed a better polymerization state, and the 28-day compressive strength reached 93 MPa, an increase of 30.9 % compared to the undoped group. The formation of zeolite-like aluminosilicates in AACG cementitious materials peaked at 1 % SO₃ doping. Additionally, at 2 % doping, the proportion of capillary and macropores decreased from 6 % to 3 % compared to the undoped group. This study offers new insights into the role of Fe2O3, MgO, and SO3 in AACG and establishes a scientific foundation for the efficient utilization of coal gangue from various sources.